2012
DOI: 10.1016/j.virol.2011.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Dengue hemorrhagic fever-associated immunomediators induced via maturation of dengue virus nonstructural 4B protein in monocytes modulate endothelial cell adhesion molecules and human microvascular endothelial cells permeability

Abstract: We previously demonstrated that dengue virus (DENV) nonstructural 4B protein (NS4B) induced dengue hemorrhagic fever (DHF)-associated immunomediators in THP-1 monocytes. Moreover, cleavage of NS4AB polyprotein by the NS2B3 protease, significantly increased immunomediator production to levels found after DENV infection. In this report using primary human microvascular endothelial cells (HMVEC) transwell permeability model and HMVEC monolayer, we demonstrate that the immunomediators secreted in the supernatants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 73 publications
0
35
0
1
Order By: Relevance
“…NS2A, NS2B, NS4B and NS5 proteins have been shown to interfere with type I interferon (IFN) signaling [12,13]. NS5 and NS4B have been demonstrated to induce the production of chemokines and proinflammatory mediators [14,15]. NS proteins are important targets of the cell mediated immune system, especially CD8+ T cells.…”
Section: Dengue Viruses and Dengue Clinical Manifestationsmentioning
confidence: 99%
“…NS2A, NS2B, NS4B and NS5 proteins have been shown to interfere with type I interferon (IFN) signaling [12,13]. NS5 and NS4B have been demonstrated to induce the production of chemokines and proinflammatory mediators [14,15]. NS proteins are important targets of the cell mediated immune system, especially CD8+ T cells.…”
Section: Dengue Viruses and Dengue Clinical Manifestationsmentioning
confidence: 99%
“…Regarding other DENV NSPs, the expression of NS5 was shown to promote the induction of IL-8 expression and secretion in HEK293-transfected cells [56], and both NS5 and NS4B induce the secretion of immunomediators in THP-1 monocytes, being this action enhanced when NS4B is linked to the 2K peptide [57]. In addition, it was observed that the conditioned media of 2K-NS4B-transfected THP1 cells contained IL-8 and TNFα in levels that induce endothelial cell permeability and increased expression of adhesion molecules [58]. NS5 also interacts with death-domain-associate protein (Daxx), a transcription repressor shown to be important to induce expression of the cytokine RANTES [59].…”
Section: Participation Of Denv Nsps In Dengue Physiopathologymentioning
confidence: 99%
“…Few articles have associated the increased vascular permeability observed in primary endothelial cells with the presence of particular mediators, like the high-mobility group box 1 protein (HMGB1) (53), the macrophage migration inhibitory factor (MMIF) (54), IL-8 (55), matrix metalloproteinase 9 (MMP-9) (56), and the nonstructural protein 4 (NS4B) of DENV (57). Regarding DENV infection and cytokines, TNF-␣, IL-6, IL-8, IL-10, and IL-12 are thought to be associated with potentially fatal plasma leakage (17), and some of these soluble factors are known to alter barrier permeability in epithelial or endothelial cells in vitro (58)(59)(60).…”
Section: Figmentioning
confidence: 99%